Orville Adelbert Derby e o mapeamento de São Paulo ( 1886 - 1905 ) - Silva, Djalma Pedro da (2006)
This study focuses on the Geographical and Geological Commissionof São Paulo, directed by American Geologist, Orville A. Derby (1851-1915), The the geographical surveys through method of geodesic triangulation, carried commission, between 1886 and 1905, Derby intended to use natural resources according to a long term plan, which would avoid danger in nature. This study intends alto to point out he role played by cartography in the history of science in Brazil